Analysis of the influence of technological parameters of steel smelting in top blowing oxygen converters on metal oxidation (Modern Problems of Metallurgy, 2020)
The article considers the influence of technological steelmaking parameters in an oxygen converter on the oxygen content in steel before tapping. Today, CELOX is an effective, but at the same time expensive method for measuring the oxygen content in steel. The information obtained using this device allows you to accurately determine the ferroalloys consumption for deoxidation of steel. Since the oxygen content in steel before production directly affects the ferroalloys and aluminum consumption, necessary for steel deoxidation, the aim of this work was to create a mathematical model that allows determining the oxygen content in steel before tapping, taking into account the controlled melting parameters. The object of the study was a top blowing oxygen converter of 60 t capacity. The following analysis was carried out for 3PS steel grade. To create a mathematical model, the factors that have the greatest influence on the oxygen content in steel before tapping were previously selected by the method of correlation analysis. Such factors included the carbon, manganese, sulfur and phosphorus content in steel before tapping, its temperature and specific consumption of oxygen. Using the method of multiple regression analysis, a mathematical model was determined, which allows determining the oxygen content in steel before tapping at the end of each melt. Comparison of the actual data on the oxygen content in steel before tapping with the results of calculation using the model showed their high convergence, which confirms the adequacy of the obtained model. The application of the developed mathematical model for predicting the oxygen content in steel before tapping in a real metallurgical enterprise will allow reduce consumption of ferroalloys and alumina for deoxidation of crude steel.
Keywords: oxidation of steel, oxygen converter, top blowing, deoxidation, alloying